Food tax policies in Pacific Island Countries and Territories: systematic policy review - Emilee Walby; Amanda C Jones; Moira Smith; Elisiva Na'ati; Wendy Snowdon; Andrea M Teng (Cambridge University Press, 2024)
Abstract Objective: To systematically identify and review food taxation policy changes in Pacific Island Countries and Territories (PICTs). Design: Food taxation polices, regarding excise taxes and tariffs applied from 2000 to 2020 in twenty-two PICTs, and their key characteristics were reviewed. The search was conducted using databases, government legal repositories and broad-based search engines. Identified documents for screening included legislation, reports, academic literature, news articles and grey literature. Key informants were contacted from each PICT to retrieve further data and confirm results. Results were analysed by narrative synthesis. Setting: Noncommunicable diseases (NCD) are the leading cause of premature death in PICTs and in many jurisdictions globally. An NCD crisis has been declared in the Pacific, and food taxation policy has been recommended to address the dietary risk factors associated with. Progress is unclear. Results: Of the twenty-two PICTs included in the study, fourteen had food taxation policies and five introduced excise taxes. Processed foods, sugar and salt were the main target of excise taxes. A total of eighty-four food taxation policy changes were identified across all food groups. There was a total of 279 taxes identified by food group, of which 85 % were tariffs and 15 % were excise taxes. Individual tax rates varied substantially. The predominant tax design was ad valorem, and this was followed by volumetric. Conclusions: A quarter of PICTs have introduced food excise taxes from 2000 to 2020. Further excise taxes, specifically tiered or nutrient-specific designs, could be introduced and more systematically applied to a broader range of unhealthy foods.